Artificial Immune Cell, AI‐cell, a New Tool to Predict Interferon Production by Peripheral Blood Monocytes in Response to Nucleic Acid Nanoparticles. Issue 46 (10th October 2022) - Chandler, Morgan; Jain, Sankalp; Halman, Justin; Hong, Enping; Dobrovolskaia, Marina A.; Zakharov, Alexey V.; Afonin, Kirill A.
Abstract: Nucleic acid nanoparticles, or NANPs, rationally designed to communicate with the human immune system, can offer innovative therapeutic strategies to overcome the limitations of traditional nucleic acid therapies. Each set of NANPs is unique in their architectural parameters and physicochemical properties, which together with the type of delivery vehicles determine the kind and the magnitude of their immune response. Currently, there are no predictive tools that would reliably guide the design of NANPs to the desired immunological outcome, a step crucial for the success of personalized therapies. Through a systematic approach investigating physicochemical and immunological profiles of a comprehensive panel of various NANPs, the research team developes and experimentally validates a computational model based on the transformer architecture able to predict the immune activities of NANPs. It is anticipated that the freely accessible computational tool that is called an "artificial immune cell, " or AI‐cell, will aid in addressing the current critical public health challenges related to safety criteria of nucleic acid therapies in a timely manner and promote the development of novel biomedical tools. Abstract : Nucleic acid nanoparticles, or NANPs, can be utilized to communicate with the human immune system, but their immunostimulatory effects can only be evaluated after their design and assembly. AI‐cell is a computational model serving as an "artificial immune cell" to drive NANP designing principles based on predictions built from a comprehensive panel of NANP physicochemical and immunological profiles.